Vom Wesen des Grundes - Heidegger, Martin 1889-1976 (Frankfurt am Main Klostermann, 1955)
An important and influential lecture course that the author gave in 1955-56, which takes as its focal point Leibniz's principle: nothing is without reason. This work shows that the principle of reason is in fact a principle of being. It also contains important discussions of language, translation, reason, objectivity, and technology.
Keywords: Philosophy